Synthesis of water soluble CdS nanoparticles and study of their DNA damage activity - Prasad, K. S.; Amin, T.; Katuva, S.; Kumari, Madhu; Selvaraj, Kaliaperumal (Arabian Journal of Chemistry, 2017)
This study reports a novel method for preparation of water soluble CdS nanoparticles using leaf extract of a plant, Asparagus racemosus. The extract of the leaf tissue which worked as a stabilizing and capping agent, assisted the formation of nanoparticles. Nanoparticles were characterized using a UV–vis spectrophotometer, Photoluminescence, TEM, EDAX, XRD and FT-IR. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, CdS of diameter ranging from 2 to 8 nm. X-ray diffraction studies showed the formation of 1 1 1, 2 2 0 and 3 1 1 planes of face-centered cubic (fcc) CdS. EDAX analysis confirmed the presence of Cd and S in nanosphere. The cytotoxicity test using MTT assay as well as DNA damage analysis using comet assay revealed that synthesized nano CdS quantum dots (QDs) caused less DNA damage and cell death of lymphocytes than pure CdS nanoparticles.